Unraveling the complexities: morpho-physiological and proteomic responses of pearl millet (Pennisetum glaucum) to dual drought and salt stress - Sithole, Charlie; Sinthumule, Rotondwa Rabelani; Gaorongwe, Joseph Lesibe; Ruzvidzo, Oziniel; Dikobe, Tshegofatso Bridget (Frontiers in Plant Science, 2025)
Agriculture is crucial for sustaining the world’s growing population, however various abiotic and biotic stressors, such as drought and salt, significantly impact crop yields. Pearl millet, a nutrient-rich and drought-tolerant crop, is essential as a food source in arid regions. Understanding its response mechanisms to drought and salt stress is important for devising strategies for improved crop performance under water deficit and saline environments. This study investigated the pearl millet’s morphological, physiological, and molecular responses subjected to individual and combined drought and salt stresses for 25 days. Significant reductions in morphological traits, such as plant height, shoot and root fresh weights and lengths, and leaf numbers were observed. Furthermore, key physiological parameters, including chlorophyll content, stomatal conductance, photosynthesis, and transpiration rates notably declined, indicating a complex interaction between stress factors and water regulation mechanisms. Protein expression analysis showed differential upregulation and downregulation patterns between the control and stressed pearl millet plants. Gene ontology mapping identified key biological processes, molecular functions, and cellular components of differentially expressed proteins associated with individual and combined stresses. Notably, a high number of unclassified proteins were identified, indicating the presence of potentially novel proteins involved in stress adaptation. Catalytic and binding activities were the predominant molecular functions detected across treatments suggesting their central role in stress response. These highlighted potential mechanisms of tolerance and adaptation in pearl millet. Overall, this study provides a comprehensive understanding of the detrimental effects of drought and salinity on pearl millet at the morphological, physiological, and proteomic levels, uncovering previously unexplored proteomic responses. These insights offer valuable molecular marker targets for breeding programs aimed at enhancing stress tolerance in pearl millet and related crops.